THE INFLUENTIAL FACTORS OF SOCIETY DELAY IN ACCOMPLISHING THE RENOVATION OF THEIR HOUSE AFTER EARTHQUAKE OCCURRED ON SEPTEMBER 30, 2009 AT THE VILLAGE OF SICINCIN, 2 X 11 ENAM LINGKUNG DISTRICT OF PADANG PARIAMAN REGENCY - Devita, Septira; Ahmad, Ridwan; Thesiwati, Aslan Sari (Pendidikan Geografi, 2013)
The earthquake 30 September 2009 occurred in West Sumatera has significant impact to the destruction of the house at the Sicincin Village about 2169 unit of the house. The destructive house got the aid from the system of rehabilitation and construction from federal through APBN (income and expenditure of nation). During 4 years, the entire of destructive house have finished to be renovated, however there were about 5-7 houses that have not finished of renovation. This research was conducted at Sicincin Village  2 x 11 Enam Lingkung District of  Padang Pariaman Regency, aim to know the influential factors of society delay in accomplishing the renovation of their house After Earthquake occurred on September 30, 2009 at the village of Sicincin, 2 x 11 Enam Lingkung District of  Padang Pariaman Regency both from the side: Variabel (1) the price of construction material, (2) income level, (3) amount of family at Sicincin Vilage, 2 x 11 Enam Lingkung District of  Padang Pariaman Regency.            The type of this research was statistic descriptive or quantitative descriptive. The population of research 579 household leader, thus sample of respondent was taken by using proportional random sampling with the proportion of 20% therefore the total of sample about 116 respondents who have heavy broken house who have delayed to renovate their house After Earthquake occurred on September 30, 2009.The research found that: 1) the price of construction material was 90,52% up the average price fall into higher price category. 2) The distribution of people income was about Rp. 1.262.000,-, average score fall to the lower income category. The distribution of total family variable was 66,3%, up the average score of existing household about 85,3% of totally larger family. It showed that the construction material price, income level, amount of family member can be factor which caused the delay of people in accomplishing their house renovation after the earthquake 30 September 2009 at Sicincin village, 2 x 11 Enam Lingkung District of  Padang Pariaman Regency.